Complex Decongestive Physiotherapy Treats Skin Changes like Hyperkeratosis Caused by Lymphedema - Hande Kaba; Yesim Bakar; Özlem Çinar Özdemir; Seda Sertel (Hindawi Limited, 2012)
Lymphedema is a chronic, progressive, and often debilitating condition. Primary lymphedema is a lymphatic malformation developing during the later stage of lymph angiogenesis. Secondary lymphedema is the result of obstruction or disruption of the lymphatic system, which can occur as a consequence of tumors, surgery, trauma, infection, inflammation, and radiation therapy. Here, we report a 64-year-old woman presenting with hyperkeratosis, a lymphedema due to metastatic uterus carcinoma. In this paper, we present the effects of complex decongestive physiotherapy on lymphedema and hyperkeratosis.